Handling heterogeneous hybrid poplar particle sizes for sugar production. (August 2016) - Morales-Vera, Rodrigo; Bura, Renata; Gustafson, Rick
Abstract: Five chip sizes of freshly harvested hybrid poplar, ranging from 0.2 × 0.2 cm to 2.0 × 1.5 cm, plus an equal mixture of all the particles, were used to determine the influence of initial particle size on sugar recovery after steam explosion pretreatment and enzymatic hydrolysis. It was found that there is essentially no effect of particle size or particle size heterogeneity on sugar recovery. Enzymatic digestibility of solids from all the particles showed similar yields ranging from 78 to 82% glucan conversion after 72 h. The overall sugar recovery from all the samples ranged from 87 to 90% and 61–64% for glucose and xylose respectively and was not influenced by particle size. An unsteady heat transfer model was used to assess the intra-particle temperature profile of the wood during pretreatment. It was found that all the wood chips, regardless of size, are essentially isothermal. This supports the experimental result of no significant difference in sugar yields among different particle sizes. Steam pretreatment appears to be a robust method that can accommodate a wide range of particle sizes. Highlights: Chip size heterogeneity did not affect the bioconversion process. High sugar recovery yields were obtained for all particles analyzed. The particle sizes investigated were essentially isothermal during pretreatment. Steam pretreatment with SO2 can concurrently process different particle dimensions.